231k views
0 votes
How do you simplify (-4i)(7i)?

User Wladislaw
by
4.9k points

2 Answers

3 votes

For this case we must simplify the following expression:


(-4i) (7i)

We have to by definition that:


- * + = -\\- * - = +\\i ^ 2 = -1

So:


-4i * 7i = -28i ^ 2 = -28 (-1) = 28

Finally we have that the expression is equivalent to:


(-4i) (7i) = 28

Answer:


(-4i) (7i) = 28

User Ysdx
by
5.8k points
1 vote


\bf (-4i)(7i)\implies -28i^2\implies \stackrel{\textit{recall that }i^2 = -1}{-28(-1)}\implies 28

User Shreeram Bhat
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.